Assessing indirect biodiversity conservation benefits of fisheries closures in the Gulf of St. Lawrence, Canada. - Andrea Bryndum-Buchholz; Tyler D Eddy; Jonathan A D Fisher (PLoS ONE)
Marine biodiversity loss is a pressing global issue, intensified by human activities and climate change. Complementary to marine protected areas (MPAs), Other Effective Area-Based Conservation Measures (OECMs) have emerged as a key tool to mitigate this loss by providing long-term biodiversity protection. However, while OECMs primarily target specific taxa, they can also offer indirect biodiversity conservation benefits (BCBs) to a wider range of taxa. In this study, we assess the indirect BCBs of eleven OECMs in the Gulf of St. Lawrence, focusing on their role in supporting the life-history processes of commercially important species such as Atlantic halibut, Greenland halibut, and redfish. We apply an integrated assessment that combines knowledge and data previously unconnected to provide information to support OECM management. Our analysis reveals that eight of the eleven OECMs overlap with potential spawning habitats for these species, suggesting important life-history benefits. However, projected climate-driven changes in bottom temperature, oxygen concentration, and pH levels pose a threat to these habitats, potentially undermining the long-term effectiveness of OECMs. These findings underscore the need for adaptive management strategies that incorporate climate-informed ecosystem indicators and broaden the conservation focus beyond economically important species. Such approaches are crucial to ensuring that OECMs continue to provide both direct and indirect BCBs in the face of accelerating climate change, thereby contributing to global marine biodiversity conservation efforts.